IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KEDISIPLINAN PESERTA DIDIK MELALUI PEMBIASAAN SHALAT BERJAMAAH DI MAS DARUSSALAM SENGKUBANG - Sugiyanto, Sugiyanto; Ubabuddin, Ubabuddin; Risa, Risa (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
The focus of this research are: planning, implementation and evaluation of Islamic education in shaping the discipline of students through the habituation of congregational prayer at MAS Darussalam Sengkubang Islamic Boarding School in Mempawah Regency. The research approach used is qualitative with a phenomenological paradigm. The type of research used in this research is field research (Field Research). The results of this study indicate that: 1) The planning of establishing the programme of establishing Dhuha and Fard prayers in congregation at MAS Darussalam Sengkubang Mempawah includes: a. The first submission of the idea, b. The welcome of the foundation and school administrators, c. The stages of maturation and stabilisation of the idea, d. The decision of establishing the idea. Decision-making on the determination of the idea. 2) The implementation of the programme of establishing Dhuha and Fard prayers in congregation at MAS Darussalam Sengkubang Mempawah shows: a. the realisation of the implementation of the programme, b. the content of activities in the programme, c. the method of providing guidance in the programme, d. the character values that are prioritised. Character values that are prioritised. 3) Evaluation of the Programme of Establishing Fard Prayers in congregation on the formation of Islamic character.